Biased beliefs and entry into scientific careers - Ina Ganguli; Patrick Gaulé; Danijela Vuletic éCugalj (W.E. Upjohn Institute for Employment Research, 2020)
We investigate whether excessively optimistic beliefs play a role in the persistent demand for doctoral and postdoctoral training in science. We elicit the beliefs and career preferences of doctoral students through a novel survey and randomize the provision of structured information on the true state of the academic market and information through role models on nonacademic careers. One year later, both treatments lead students to update their beliefs about the academic market and impact career preferences. However, we do not find an effect on actual career outcomes two years postintervention.
Keywords: I23; D80; D84; J24; 330; higher education; information; biased beliefs; career preferences; science